2004
DOI: 10.1038/430309a
|View full text |Cite
|
Sign up to set email alerts
|

Pitch discrimination in the early blind

Abstract: Do blind people develop superior abilities in auditory perception to compensate for their lack of vision? They are known to be better than sighted people at orientating themselves by sound, but it is not clear whether this enhanced awareness extends to other auditory domains, such as listening to music or to voices. Here we show that blind people are better than sighted controls at judging the direction of pitch change between sounds, even when the speed of change is ten times faster than that perceived by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
231
1
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 370 publications
(263 citation statements)
references
References 6 publications
21
231
1
10
Order By: Relevance
“…Thus, superior performance of B large subjects over the sighted reference group (R B, large ) and both groups of visually impaired subjects (VI no and VI small ) was confirmed in our pitchtimbre categorization experiment for the two most difficult conditions. Such performance of B large group was expected on the basis of earlier reports (Bogusz et al, 2012a;Wan et al, 2010;Gougoux et al, 2004;Tervaniemi et al, 2005;Spiegel, Watson, 1984).…”
Section: Pitch-timbre Categorization Experimentssupporting
confidence: 63%
See 1 more Smart Citation
“…Thus, superior performance of B large subjects over the sighted reference group (R B, large ) and both groups of visually impaired subjects (VI no and VI small ) was confirmed in our pitchtimbre categorization experiment for the two most difficult conditions. Such performance of B large group was expected on the basis of earlier reports (Bogusz et al, 2012a;Wan et al, 2010;Gougoux et al, 2004;Tervaniemi et al, 2005;Spiegel, Watson, 1984).…”
Section: Pitch-timbre Categorization Experimentssupporting
confidence: 63%
“…According to some studies, blind people perform better than sighted individuals in tasks related to pitch discrimination and pitch-timbre categorization (Bogusz et al, 2012a;Wan et al, 2010;Gougoux et al, 2004). As some of blind and visually impaired people are musically or auditory trained, it may be interesting to determine the effect of their musical experience on the ability to solve basic psychoacoustic tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially some B&PS people might even show a stronger effect. CB and EB individuals have been shown to have a compensatory advantage in certain aspects of auditory perception, including pitch discrimination (Gougoux et al, 2004) and more efficient processing of simple auditory stimuli (Stevens & Weaver, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that adult blind or visually handicapped people perform better than sighted individuals in tasks related to attention focusing (Gougoux et al, 2004) and pitch discrimination (Gougoux et al, 2004;Wan et al, 2010), but not in the pitch memory task (Wan et al, 2010). Some papers indicate that congenitally blind or early-blind adult individuals display superior performance compared to late-blind persons (Gougoux et al, 2004;Wan et al, 2010;Voss et al, 2008).…”
Section: Introductionmentioning
confidence: 99%